2021
DOI: 10.1002/jdd.12584
|View full text |Cite
|
Sign up to set email alerts
|

Assessing price sensitivity in dental education and implications on student diversity

Abstract: Increasingly, the price of professional school is seen as a potential deterrent for interested students. Data collected by the American Dental Association (ADA) from the 66 U.S. dental schools showed the average 4‐year nonresident tuition and fees totaled $321,575 in 2018–2019, 35% greater than in 2008–2009, after adjusting for inflation. The aim of this study was to assess whether dental education pricing has impacted applications, enrollments, and yield rates, particularly among students underrepresented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Dental education is costly; a recent study utilizing data from the American Dental Association revealed that “average 4‐year nonresident tuition and fees totaled $321,575 in 2018–19” across all 66 accredited US dental schools at that time. [28] The same work highlighted underrepresented students in dentistry. African American and Hispanic/Latino students were “price‐sensitive”; that is, they were less likely to enroll in higher‐priced schools, compounding the shortage of dental graduates.…”
Section: Discussionmentioning
confidence: 97%
“…Dental education is costly; a recent study utilizing data from the American Dental Association revealed that “average 4‐year nonresident tuition and fees totaled $321,575 in 2018–19” across all 66 accredited US dental schools at that time. [28] The same work highlighted underrepresented students in dentistry. African American and Hispanic/Latino students were “price‐sensitive”; that is, they were less likely to enroll in higher‐priced schools, compounding the shortage of dental graduates.…”
Section: Discussionmentioning
confidence: 97%
“…From 2008–09 to 2018–19, the American Dental Association (ADA) reports that the average total cost of attending dental school increased by 35% after adjusting for inflation. Consequently, the average debt was 30% greater for 2019 compared to 2009 dental graduates after adjusting for inflation 14 . When discussing admissions, yield refers to how many students accept a program's admittance offer.…”
Section: Discussionmentioning
confidence: 99%
“…When discussing admissions, yield refers to how many students accept a program's admittance offer. National data collected by the ADA shows that the higher a program's tuition, the lower the yield 14 . While this suggests that applicants consider price when selecting a program, the ADA has not queried students on their reasoning for selecting a dental school.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations